Neuronal estrogen receptor-α mediates neuroprotection by 17β-estradiol - Elzer, Joachim; Muḥammad, Sajjad; Wintermantel, Tim M.; Régnier-Vigouroux, Anne; Ludwig, Jochen; Schütz, Günther; Schwaninger, Markus (Journal of cerebral blood flow & metabolism, 2010)
17β-Estradiol (E2) was shown to exert neuroprotective effects both in in vitro and in vivo models of stroke. Although these effects of E2 are known to require estrogen receptor-α (ERα), the cellular target of estrogen-mediated neuroprotection remains unknown. Using cell type-specific ER mutant mice in an in vivo model of stroke, we specifically investigated the role of ERα in neuronal cells versus its role in the microglia in the mediation of neuroprotection by estrogens. We generated and analyzed two different tissue-specific knockout mouse lines lacking ERα either in cells of myeloid lineage, including microglia, or in the neurons of the forebrain. Both E2-treated and E2-untreated mutant and control mice were subjected to a permanent middle cerebral artery occlusion for 48 h, and the infarct volume was quantified. Although the infarct volume of E2-treated female myeloid-specific ERα knockout mice was similar to that of E2-treated control mice, both male and female neuron-specific ERα mutant mice had larger infarcts than did control mice after E2 treatment. We conclude that neuronal ERα in female and male mice mediates neuroprotective estrogen effects in an in vivo mouse model of stroke, whereas microglial ERα is dispensable.